ASSESSMENT OF MOVEMENT OF THE BELEX15 INDEX USING LINEAR REGRESSION AND NEURAL NETWORK - Petrović, Marijana (Journal of process management and new technologies, 2019)
The stock market remains a focus of attention for researchers. So far, various technical and statistical methods and models have been developed and used to show different results, but none with great success. In this paper the author used two approaches to estimate price movement in stock market: simple linear regression and backpropagation neural network.The aim of this paper is to estimate the value of the Belex15 stock exchange index and to analyze its movement using two aforementioned approaches.